Lessons from the first 6 years of an intervention-based field epidemiology training programme in Papua New Guinea, 2013–2018. Issue 6 (15th December 2019) - Ropa, Barry; Flint, James; O'Reilly, Michael; Pavlin, Boris Igor; Dagina, Rosheila; Peni, Bethseba; Bauri, Mathias; Pukienei, Alois; Merritt, Tony; Terrell-Perica, Steven; Yamba, Abel; Prybylski, Dimitri; et al.
Abstract : Papua New Guinea (PNG) faces a critical shortage of human resources to address pressing public health challenges arising from an increasing burden of communicable and non-communicable diseases. PNG is an independent State in the Pacific and home to 8.2 million people. Resource and infrastructure constraints due to the country's challenging geography have made it difficult and expensive to deliver health services and implement health programmes. The National Department of Health and its partners developed a field epidemiology training programme of Papua New Guinea (FETPNG) to strengthen the country's public health workforce. The training programme covers field epidemiology competencies and includes the design, implementation and evaluation of evidence-based interventions by Fellows. From 2013 to 2018, FETPNG graduated 81 field epidemiologists. Most FETPNG graduates (84%) were from provincial or district health departments or organisations. Many of their intervention projects resulted in successful public health outcomes with tangible local impacts. Health challenges addressed included reducing the burden of multi-drug resistant-tuberculosis (TB), increasing immunisation coverage, screening and treating HIV/TB patients, and improving reproductive health outcomes. FETPNG Fellows and graduates have also evaluated disease surveillance systems and investigated disease outbreaks. Early and unwavering national ownership of FETPNG created a sustainable programme fitting the needs of this low-resource country. A focus on designing and implementing effective public health interventions not only provides useful skills to Fellows but also contributes to real-time, tangible and meaningful improvements in the health of the population. The graduates of FETPNG now provide a critical mass of public health practitioners across the country. Their skills in responding to outbreaks and public health emergencies, in collecting, analysing and interpreting data, and in designing, implementing and evaluating public health interventions continues to advance public health in PNG.